Discovery of novel phenaleno isoquinolinium-based fluorescence imaging agents for sentinel lymph node mapping. Issue 48 (1st December 2021) - Han, Ye Ri; Lee, Da-Sol; Lee, Sang Bong; Jeon, Hui-Jeon; Lee, Sijoon; Sung, Soo-Eun; Lee, Chang-Hee; Cho, Sung Jin; Kim, Kil Soo; Kim, Dong-Su; Jeon, Yong Hyun
Abstract : We reported on the development of novel fluorescent agents (called Medical Fluorophores) and their usefulness for in vivo detection in the diagnosis of sentinel lymph nodes. Abstract : Fluorescence imaging agents have recently received huge attention due to their important role in disease diagnostics. However, the intrinsic problems of these probes, such as complex synthetic routes and high molecular weight, remain challenging. Here, we developed novel phenaleno isoquinolinium-based fluorescent agents, Medical Fluorophores 37–41 (MF37-41), applicable to the quantitative and sensitive detection of sentinel lymph nodes (SLNs). These imaging agents showed no adverse effects on the proliferation of immune and normal cells and did not induce in vivo toxicity. In vivo fluorescence lifetime imaging demonstrated the accumulation of phenaleno isoquinolinium salts in the SLNs of nude mice within 15 min postinjection, consistent with our biodistribution findings. These results suggest that phenaleno isoquinolinium salts are feasible fluorescence imaging agents that can be used as potential lymphatic tracers.